2018
DOI: 10.1063/1.5049832
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric coupling and the manipulation of magnetic Bloch skyrmions

Abstract: Chiral-magnetic/ferroelectric composite systems offer the possibility of electrically inducing magnetic Bloch skyrmions [Wang and Grimson, Phys. Rev. B 94, 014311 (2016)]. They are appealing for potential applications in spintronics due to their self-protection behavior. To realize skyrmion-based spintronic devices, it is essential to control the motions of the skyrmions. In this work, we propose a mechanical technique to manipulate skyrmions collinearly with a mobile external electric field that is imposed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Skyrmions are nontrivial magnetic spin textures considered to offer better functionalities for spintronic and storage devices owing to their topological nature, which provides stability from defects and from external perturbations [8][9][10][11][12]. For example, it has been shown that skyrmions and skyrmionic structures can be displaced using relatively small current densities [12], stabilized under an applied magnetic field [13] and, when interfaced with a gate dielectric, controlled by an applied electric field [14][15][16][17]. More generally, the topological nature of a spin texture is characterized by the topological charge or skyrmion winding number [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Skyrmions are nontrivial magnetic spin textures considered to offer better functionalities for spintronic and storage devices owing to their topological nature, which provides stability from defects and from external perturbations [8][9][10][11][12]. For example, it has been shown that skyrmions and skyrmionic structures can be displaced using relatively small current densities [12], stabilized under an applied magnetic field [13] and, when interfaced with a gate dielectric, controlled by an applied electric field [14][15][16][17]. More generally, the topological nature of a spin texture is characterized by the topological charge or skyrmion winding number [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%